2018
DOI: 10.1364/oe.26.008385
|View full text |Cite
|
Sign up to set email alerts
|

Topographically induced homeotropic alignment of liquid crystals on self-assembled opal crystals

Abstract: The surface of multilayered opal crystals resulted in homeotropic alignment of liquid crystal (LC), originated from the surface topography of opal crystals rather than a chemical nature of the nanoparticles. The polar anchoring energy (5.51 × 10 J/m) of the crystal surface for nematic LC molecules was in a similar range to the conventional polyimide alignment layer (2.11 × 10 J/m) used for commercial applications. The critical length scale for anchoring transition was approximately Lw = ~1 μm. If a diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…This provided mechanical nano-groove planar alignment of the nematic liquid crystal with a negligible pretilt angle. 21 Inorganic thin solid films, for example silicon dioxide and associated solid dielectrics, commonly provide a polar anchoring energy of the order of 10 À5 J m À2 22 similar to conventional polyimide 23 and polyvinyl alcohol alignment layers. 24 Magnesium fluoride thin films have previously been used to align twisted nematic cells in the literature, giving a comparable electro-optical performance to polyimide alignment layers.…”
Section: Device Details and Preparationmentioning
confidence: 99%
“…This provided mechanical nano-groove planar alignment of the nematic liquid crystal with a negligible pretilt angle. 21 Inorganic thin solid films, for example silicon dioxide and associated solid dielectrics, commonly provide a polar anchoring energy of the order of 10 À5 J m À2 22 similar to conventional polyimide 23 and polyvinyl alcohol alignment layers. 24 Magnesium fluoride thin films have previously been used to align twisted nematic cells in the literature, giving a comparable electro-optical performance to polyimide alignment layers.…”
Section: Device Details and Preparationmentioning
confidence: 99%
“…Consequently, a surface topology change leads to a HA state by inducing a sufficient degree of elastic distortion to surpass the effects of surface anchoring. 15 The evidence about the surface morphology is going to be dealt with in surface analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is supported by our observation that chloroform-treated 140 nmthick brushes, which exhibit an rms roughness of 2.1 ± 0.2 nm, induces planar LC alignment, while chloroform-treated 12 nmthick brushes, which exhibit an rms roughness of 2.3 ± 0.2 nm, induce homeotropic alignment. Prior studies 45 have reported that surface roughness can influence the orientations of LCs, but those studies employed surfaces with rms roughness values that were much larger than 2 nm.…”
Section: Resultsmentioning
confidence: 99%